Online Adaptive Neuro-Fuzzy Inference Based SVC Control Strategy for Stability Enhancement in Two-Machine Power System - Nguyen, Thi Mi Sa (Old Journal, 2018)
An online auxiliary control was designed for Static Var Compensator (SVC) to improve the poorly damped oscillations in power system subjected to large disturbances. This paper presents auxiliary control based on Adaptive Neuro-Fuzzy Inference (ANFIS) control using triangular membership function. Such a model free based control does not require any prior information about the system and is robust to system changes quickly. The time domain simulation results were carried out for two machine test system for two different cases. In order to exploit the performance and robustness of ANFIS control, the results were compared with conventional PI. Controler simulation results and performance indices reveal that the proposed control outperforms during various fault conditions and hence improves the transient stability to a great extend.